Preliminary Findings of Fecal Gonadal Hormone Concentrations in Six Captive Sea Otters (Enhydra lutris) after Deslorelin Implantation. Issue 3 (2nd July 2012) - Larson, S.; Belting, T.; Rifenbury, K.; Fisher, G.; Boutelle, S. M.
<x xml:space="preserve">Abstract</x> The sea otter (Enhydra lutris) is a popular exhibit animal in many zoos and aquariums worldwide. Captive sea otters from these populations are owned by the United States Fish and Wildlife Service (USFWS). The USFWS has requested that these sea otters be prevented from breeding in order to save captive space for wild rescued animals. Sea otters are often housed in mixed sex groups, therefore a chemical contraceptive method or surgical removal of gonads must be used to prevent potential pregnancy. The contraceptive, Suprelorin® or deslorelin, has been used in many different species to effectively suppress reproduction but duration of effect may vary not only between species but also individuals. Here, we report the effects of one to several consecutive deslorelin implants on gonadal reproductive hormones found in fecal samples from six captive sea otters (two males and four females) compared to two control otters (one male and one female) housed at three zoological institutions. We documented the longitudinal hormone signatures of many stages of the contraceptive cycle including pretreatment (PT), stimulatory phase (S), effective contraception (EC), and hormone reversal (HR) that was characterized by a return to normal hormone levels. Deslorelin was found to be an effective contraceptive in sea otters and was found to be reversible documented by a live birth following treatment, however the duration of suppression in females was much longer than expected with a 6‐month and a 1‐year implant lasting between 3 and 4 years in females. Zoo Biol. 32:307–315, 2013. © 2012 Wiley Periodicals, Inc.